2001
DOI: 10.1002/nme.177.abs
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel algorithm for the adaptive calculation of transient stratified flow of gas, oil and water in pipelines

Abstract: SUMMARYIn this paper, a mathematical model for three-phase ow in pipelines is developed and a novel algorithm for solving the resulting system of partial di erential equations is presented. The numerical solution is based on an adaptive mesh reÿnement technique. Signiÿcant gains in the numerical performance have been achieved by using this technique combined with high-resolution schemes like FCT. This approach is highly beneÿcial in terms of speed while preserving accuracy. An explicit adaptive numerical solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We suggested that the velocity distribution of the flow could be extracted by monitoring the movement of the brightness pattern in the image sequence of the pipe flow. Only with the equation (1), however, we can't work out the movement simply because there are two unknowns with the equation. According to the nature of the general fluid flow, we suggested that each element of the flow should travel in the similar direction of its neighboring elements and therefore the directional smoothness constraint [13].…”
Section: From Optical Flow To Liquid Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggested that the velocity distribution of the flow could be extracted by monitoring the movement of the brightness pattern in the image sequence of the pipe flow. Only with the equation (1), however, we can't work out the movement simply because there are two unknowns with the equation. According to the nature of the general fluid flow, we suggested that each element of the flow should travel in the similar direction of its neighboring elements and therefore the directional smoothness constraint [13].…”
Section: From Optical Flow To Liquid Flowmentioning
confidence: 99%
“…Multiphase pipeline flow is not only very important to oil, gas and process industry but also very complex and scientifically challenging. In the context of the flow in pipeline, the multiphase flows of interest are simulated using one-dimensional transient mathematical models [1] [2][3]. This is a class of problems where comprehensive simulations, although desirable on physical grounds, are not practical due to the large aspect ratio between the pipes length and diameter.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative treatment can be applied for a stratified flow with gas at top, oil at the middle and water at bottom. This can be done for immiscible liquids (Taitel et al, 1995;Hanich,Thompson, 2001;Zhang, Sarica, 2005;Ghorai et al, 2005;Neogi et al, 1994). For example, Taitel et al (1995) developed a one dimensional model based on mass and momentum balances to calculate gas, oil, and water hold-ups, pressure and velocities.…”
Section: Introductionmentioning
confidence: 97%
“…Babakhani 2017 The most common flow pattern for oil-water-gas flows is slug flow, where a series of liquid slugs is separated by relatively large gas pockets. Up to our knowledge, there are few theoretical studies to characterize flow behavior of oil-water-gas flows, which is mostly related to stratified flow regime (see Taitel et al, 1995, Khor et al, 1997, Hanich and Thompson, 2001. Taitel et al (1995) presented a theoretical approach for three layer stratified flow of liquid-liquid-gas to compute liquid and gas holdup.…”
Section: Introductionmentioning
confidence: 99%